The First Case of Cutaneous Acanthamoebiasis Caused by Acanthamoeba triangularis in Korea - Choi, Mi Soo; Myong, Na Hye; Seo, Min; Jang, Sukbin; Yun, Dae Kwan; Yeom, Kyujin; Chung, Dong-Il; Park, Byung Cheol; Hong, Yeonchul; Kim, Myung Hwa (Annals of dermatology, 2023)
A 62-year-old man with multiple myeloma visited our clinic with multiple painful erythematous to purpuric nodules on his whole body. He received a skin biopsy which showed septal and lobular inflammation with vasculitis, and multiple amoebic organisms were found. Polymerase chain reaction and culture were performed and an infection was diagnosed. This is the first report on cutaneous acanthamoebiasis caused by , suggesting that should be regarded as a clinical pathogen that can cause ocular as well as disseminated infection.